Peptides Targeting the Interaction Between Erb1 and Ytm1 Ribosome Assembly Factors - Orea-Ordóñez, Lidia; Masiá, Susana; Bravo, Jerónimo (Frontiers in Molecular Biosciences, 2021)
Ribosome biogenesis is an emerging therapeutic target. It has been proposed that cancer cells are addicted to ribosome production which is therefore considered as a druggable pathway in cancer therapy. Cancer cells have been shown to be more sensitive to inhibition of the ribosome production than healthy cells. Initial attempts of inhibiting ribosome biogenesis have been focusing on inhibition of transcription by targeting RNA Pol I. Despite being a promising field of research, several limitations have been identified during development of RNA Pol I inhibitors, like the lack of specificity or acquired resistance. Ribosome biogenesis is a multistep process and additional points of intervention, downstream the very initial stage, could be investigated. Eukaryotic ribosome maturation involves the participation of more than 200 essential assembly factors that will not be part of the final mature ribosome and frequently require protein-protein interactions to exert their biological action. Using mutagenesis, we have previously shown that alteration of the complex interface between assembly factors impairs proper ribosome maturation in yeast. As a first step towards the developing of ribosome biogenesis inhibitory tools, we have used our previously solved crystal structure of the Chaetomium thermophilum complex between the assembly factors Erb1 and Ytm1 to perform a structure-guided selection of interference peptides. The peptides have been assayed in vitro for their ability to bind their cellular partner using biophysical techniques.